If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(r + 1) + -1r = -2 + 4 Reorder the terms: 2(1 + r) + -1r = -2 + 4 (1 * 2 + r * 2) + -1r = -2 + 4 (2 + 2r) + -1r = -2 + 4 Combine like terms: 2r + -1r = 1r 2 + 1r = -2 + 4 Combine like terms: -2 + 4 = 2 2 + 1r = 2 Add '-2' to each side of the equation. 2 + -2 + 1r = 2 + -2 Combine like terms: 2 + -2 = 0 0 + 1r = 2 + -2 1r = 2 + -2 Combine like terms: 2 + -2 = 0 1r = 0 Solving 1r = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Divide each side by '1'. r = 0 Simplifying r = 0
| 103x+34=52 | | -3y+4=10 | | .87/1 | | 9/2z-7/3=41/6 | | -5-5j=-4j | | K-14=-18 | | -54=16x+312 | | 4(x+5)=3(x-11) | | (5h+2)=-8 | | 3g-8=-2+2g-10 | | 25=x-16 | | -3h+12=-7h-9-16 | | 9(x-14)=35-7(x+5) | | 24x•35y/25x | | (b+9)=2 | | 14.4=-2.7x-1.8 | | 7p-10=9p+6 | | (3z-3)=9 | | 1.4x-5.6=2.8 | | ax-ab=bx | | 5u=7+6u | | 15-x-9=21 | | 2=11+3a | | 7d-10=8(d-3) | | 4(x+3)=-6(7+5x)+34x | | -8d=5-7d | | 45=-25+32x | | -b=-2b+4 | | 4(w-3)=-9w-38 | | 400-16u=15u+18+6 | | -4+3w=-7+6w | | F(5)=6 |